Patrolling the largest drug market on the eastern seaboard: a synthetic control analysis on the impact of a police bicycle unit - Lawrence, Daniel S. (Criminology & public policy, 2023)
Research Summary This study employed a microsynthetic control method to evaluate the impact of the newly introduced bicycle patrol unit in the Kensington neighborhood of Philadelphia, which is well-known as a major drug market. The findings reveal that the bicycle patrol unit led to a notable reduction in social disorder crimes, which was one of the primary objectives of the patrol officers. However, it also resulted in a significant increase in the number of narcotic crimes, violent person crimes, and shooting offenses. The amount of total crimes and property crimes remained unchanged. Policy Implications Bicycle patrols can effectively reduce street-level disorder and increase police efforts to arrest drug offenders and remove drugs from the streets. However, the introduction of this police activity may disrupt the normal operation of drug markets, which can lead to increased violence from instability in the street-level drug business. Therefore, departments should conduct detailed crime analyses and gather intelligence alongside directed patrols to better understand and respond to the potential consequences of their interventions.